Effective Teaching as Described by Teachers who Are Also Doctoral Students: A Qualitative Descriptive Study - Kelly R. Maguire; Amy M. Anderson (Journal of Scholarly Engagement)
Teachers’ roles in their students’ lives cannot be underestimated because they impact students in various ways. However, what makes a good teacher is often based on personal perspectives and values, making it subjective. This qualitative descriptive study sought to explore how teachers, who are also students or recent graduates of a teaching and learning doctoral degree program, define effective teaching and describe the characteristics of effective teachers. Data were collected using semi-structured, conversational interviews. The findings revealed that effective teachers exemplify three characteristics: rapport, communication, and passion. Recommendations for practitioners and future research are included.